Un-tensioned pullout tests to predict the bond quality of different prestressing reinforcements used in concrete railroad ties - Arnold, Matthew Lukas (Kansas State University, 2013)
An experimental testing program was conducted at Kansas State University (KSU) to test the bond characteristics of various 5.32-mm-diameter steel wires and smaller diameter (less than 0.5 in.) strands used in prestressed concrete railroad ties. A total of 13 wires and six strands produced by seven different steel manufacturers were used during this testing. Since no wire bond pullout test currently exists, one was developed and its validity tested. This un-tensioned pullout test could serve as a quality control test similar to the standard test for strand bond (ASTM A1081) that has been developed for pretensioned strands. This strand test is currently not verified for strands less than 0.5-in. in diameter, so the procedure was also scrutinized using strands common in the concrete railroad tie industry. Some of the wires and strands contained surface indentations. It is generally accepted that indentations in the reinforcements improve the bond between the steel and concrete. To further complicate the issue, reinforcements with different surface conditions (rust, oils, lubricants) are allowed to be used in the concrete ties which further affects the bond quality of the reinforcements. However, no standardized indentation patterns (shape, size, depth of indent, etc.) or surface conditions (degree of rusting, amount of surface lubricants, etc.) are utilized by all wire and strand manufacturers. Thus, the corresponding bond behavior of these different reinforcements when placed in various concrete mixtures, in terms of average transfer lengths and typical variations, is essentially unknown. The purpose of this testing program was to develop (in the case of wires) or verify/develop (in the case of strands) a pullout testing procedure predictive of the reinforcement’s bond performance in a prestressed application. The test should be relatively inexpensive, demonstrably repeatable, and easily reproducible. Results from the un-tensioned pullout tests were compared to transfer length measurements from accompanying pretensioned concrete prisms in the lab. Additionally, pullout tests and transfer length measurements were obtained at an actual concrete railroad tie manufacturing plant. The obtained data was compared to the lab data and analyzed to further understand the relationship between un-tensioned pullout tests and pretensioned concrete members.
Keywords: Pullout test; Transfer length; Bond; Concrete railroad ties; Quality control; Prestress; Civil Engineering (0543)